Analisis Penerapan Good Governance Melalui Pelaksanaan Pengawasan Partisipatif Berbasis Komunitas Pada Pilkada 2024 Di Kabupaten Lamongan (Studi Kasus: Komunitas Disabilitas) - Nadiasel Ogsala; Farid Ma'ruf, Muhammad; Wahyu Pradana, Galih; Febriyan Eprilianto , Deby (Universitas Negeri Surabaya, 2026)
Groups of people with disabilities are one of the vulnerable groups of society that are targeted for strengthening participatory supervision in the 2024 elections. This is stated in Bawaslu Regulation No. 2 of 2023. Although national regulations have emphasized the involvement of people with disabilities, their implementation at the regional level of Lamongan Regency still faces various obstacles to participation. This study aims to analyze the extent to which the General Election Supervisory Agency (Bawaslu) has applied the principles of good governance through community-based participatory supervision in Lamongan Regency which has the largest number of people with disabilities in East Java. This study uses a descriptive qualitative method with case studies as a research approach. Data were collected through in-depth interviews, field observations, and studies of literature, documentation, and analyzed using Griffin's theory of supervisory process principles, which were then strengthened by the use of Pasolong's theory of good governance. The results of the study show that the involvement of disability groups is still very minimal in a series of participatory supervision processes in Lamongan Regency in the 2024 Regional Elections. The main obstacle is found in the lack of strengthening of plans and benchmarks of activity standards so that the resulting outcomes cannot describe the success of the participatory supervision program. This study recommends strengthening more inclusive standards, measuring sustainable programs, and improving Bawaslu's performance in order to encourage the formation of an adequate companion community. Keywords: participatory supervision, disability community, participation, good governance